ESTRACUCULAR ACTIVITIES PROGRAM IN SCHOOLS TO INCREASE STUDENTS' INTEREST IN LEARNING - Dara Gustia Amsah; Nur Djarotu Syifa Azmi; Dila Nursyafitri (CV. Asry Persada Quality, 2024)
The type of research used in this research is qualitative research. The data collection techniques carried out in this research are as follows: (1) Observation (Observation, documentation and traiangulation. The results of scout research are using things that can provide a deterrent to students so they don't repeat themselves. the mistakes he made. Apart from using punishment, interest in learning uses games that can sharpen students' mindsets so that they have a brave attitude and mentality to move forward. The interest in learning carried out by the coach is also through habits carried out by the coach such as not being late when leaving, always obey the rules, always be disciplined in carrying out tasks and there are many other habits that scout leaders implement to stimulate interest in learning in students.